Józefa Tischnera rozumienie pracy - Zywar, Gabriela (Annales. Etyka w Życiu Gospodarczym, 2011)
Work cannot be separated from human life. Nowadays, the concept of work has been usually perceived only from an economicperspective as a factor of production process. Does acquiring the means of livelihood is the only value of human work? No doubt, it is a verybasic goal, but not the only one. Besides this dimension, there are many other important aspects of human work.In the first part of my paper, I point out two possible understanding of the phenomenon of human work– an objective and a subjective one. The objective sense has to show haw men reign over the earth (material production). The subjective oneemphasizes the dignity of human person (philosophical anthropology and ethics). According to Tischner it would be a mistake to take intoaccount only the objective meaning of work, since the moral sense would have been omitted.In the second part, I will adduce the dangers to the proper understanding of human work which arise when one chooses the wrongconcept of man (philosophical anthropology). In the philosophical understanding, work is a derivative of the accepted vision of man. In orderto avoid the situation of objectifying of man (problem of reification), we should conceive him as a personal being who crates himself in theprocess of work.In the final part of my presentation, the phenomenon of work is discussed as a mean of improvement and perfection of human beingwhich is done in cooperation with others. By the means of work man enters into relations with God, with the material world, with others(the social world) and with himself. By the above mentioned means she discovers the purpose of her life.